2007
DOI: 10.1097/mpg.0b013e318043c097
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Adaptive Th2 Immunity with Eotaxin‐3/C‐C Chemokine Receptor 3 in Eosinophilic Esophagitis

Abstract: Collectively, these studies demonstrate cooperation between systemic CD4+ Th2-cell-mediated immunity and an enhanced eosinophil-CCR3/eotaxin-3 pathway in EE pathogenesis. Furthermore, the imbalanced Th2 immunity and increased CCR3 expression are reversible with disease remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 50 publications
(74 reference statements)
3
72
1
Order By: Relevance
“…IL-5 mRNA is increased in the biopsies of EE patients compared to NL patients ( (28,29) and unpublished data). Peripheral CD4+T cells show an increase in intracellular IL-5 in the blood of EE patients compared to non-atopic non-EE patients (10). Determining the role of IL-5 in EE is of importance since two independent studies have shown an improvement in the clinical and/or pathological symptoms of EE after anti-IL-5 treatment (30-32).…”
Section: Molecular Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…IL-5 mRNA is increased in the biopsies of EE patients compared to NL patients ( (28,29) and unpublished data). Peripheral CD4+T cells show an increase in intracellular IL-5 in the blood of EE patients compared to non-atopic non-EE patients (10). Determining the role of IL-5 in EE is of importance since two independent studies have shown an improvement in the clinical and/or pathological symptoms of EE after anti-IL-5 treatment (30-32).…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Thus, the immune responses in EE are characterized by enhanced production of Th2-associated cytokines in response to both food and environmental allergens. Finally, in a recent study examining intracellular staining of PBMC cytokines and cytokine production after stimulation in EE patients, the systemic parameters of EE patients were highly similar to atopic non-EE patients (10).…”
mentioning
confidence: 99%
“…Moreover, it has also been demonstrated that the inflammatory response in EoE patients is restricted to the esophagus and does not involve the stomach and/or duodenum [10]. The Th2-type inflammatory profile of EoE was subsequently confirmed in pediatric and adult EoE [12], and relevant allergens were identified for both pediatric and adult EoE [11,13]. Moreover, a strong link between atopy and EoE was subsequently described in both pediatric and adult EoE patient groups [14,15].…”
Section: Cells and Cytokinesmentioning
confidence: 99%
“…Genome-wide microarray expression studies have shown that the gene-encoding eotaxin-3 is the most highly induced gene in EoE patients compared to healthy individuals [43] . Furthermore, a single-nucleotide polymorphism in the human eotaxin-3 gene seems to be associated with disease susceptibility and mice deficient in the eotaxin receptor were protected from experimental EoE [63,64] . Eosinophils are born from the bone marrow progenitor stem cells under the influence of interleukin-3 (IL-3), interleukin-5 (IL-5) and granulocyte-macrophage colony-stimulating factor (GM-CSF).…”
Section: Genetic Vs Environmental Etiological Factorsmentioning
confidence: 99%
“…Similarly to GERD patients with esophagitis [60,61] , EoE is associated with high levels of cytokines particularly IL-3, IL-5, IL-13, increase production of eotaxin chemokines CCL11, CCL24 and CCL26 (or eotaxins 1, 2 and 3 respectively) that attract inflammatory cells, predominantly eosinophils [62,63] . Studies performed in esophageal rings showed that stimulation of the rings with IL-13 for 48 h resulted in a significant attraction of eosinophils into the lower chamber containing TH-2 lymphocytes while chambers containing only IL-13 did not [64,65] . These data demonstrate that IL-13 supports eosinophil migration and that CCL11 and CCL24 also are both important in promoting eosinophil infiltration [66,67] .…”
Section: Genetic Vs Environmental Etiological Factorsmentioning
confidence: 99%